Subnational investment in human capital - Marcus Manuel; Dan Coppard; Amy Dodd; Harsh Desai; Richard Watts; Zach Christensen; Stephanie Manea (Overseas Development Institute (ODI), 2019)
Delivering on the global commitment to leave no one behind means development thinking must undergo a transformational shift to address inequalities within countries, as well as between countries. This report, jointly prepared with Development Initiatives, reviews how well public finance is targeted at subnational level. It covers investment in human capital, spending on health and education, by both government and donors in all of the 82 poorest countries - that is all low- and lower middle-income countries and least developed countries. The first key finding is that there is little evidence from the data that is publicly available that either government or donors are responding to the distribution of poverty within countries. On average poorer regions receive 15% less than the national average for government spending on education. The second key finding is that data on how finance is allocated at the subnational level is extraordinarily lacking. Only one in seven countries publishes adequate budget data and only one in eleven adequate aid data. The report notes simple improvements could be made and sets out two recommendations to improve targeting and increase transparency.
Keywords: 330